Searching for Low Cost Alternative Energy Source: An Analysis of Pakistan Sugar Industry - Memon, Manzoor Hussain; Ahmed, Nadeem; Larik, Engr. Raja Masood (Growth, 2017)
Pakistan is searching for alternative energy sources owing to perpetual power crisis in the country. Stylized facts suggest that there is a strong correlation between energy consumption and economic growth, while more economic activity leads to more employment and contributes to reduce poverty. Supply dynamics considered as major cause of energy crisis in Pakistan. Sugar industry in Pakistan is assumed as an opportunity and potential for alternative energy production. This paper is an attempt to explore the alternative source of energy generation by using latent potential of sugar industry and explore the possibility of having surplus production and generation of electricity for national grid. Bagasse, a residual by-product from sugarcane is traditionally used for generation of electricity in the industry to meet its own energy needs. In addition to the analysis of potentiality of the industry, the economic analysis is also carried out from the perspective of foreign exchange saving that have been used to import furnace oil for power generation. From the retrospective analysis, it is revealed that country could save minimum 242 million dollars during the sugar season that is almost one fourth of the total furnace oil import of the country during the same period.